Improvement of the management of residual waste in areas without thermal treatment facilities: A life cycle analysis of an Italian management district. (October 2015) - Di Maria, Francesco; Micale, Caterina; Morettini, Emanuela; Sisani, Luciano; Damiano, Roberto
Highlights: LCA analysis of two option for residual waste management. Exploitation of mechanical physical sorting facility for extracting recyclable from RMSW. Processing the mechanically sorted organic fraction in bioreactor landfill. Sensitivity analysis demonstrate high influence for impact assessment of substitution ratio for recycle materials. Abstract: Starting from an existing waste management district without thermal treatment facilities, two different management scenarios for residual waste were compared by life cycle assessment (LCA). The adoption of a bioreactor landfill for managing the mechanically sorted organic fraction instead of bio-stabilization led to reduction of global warming and fresh water eutrophication by 50% and 10%, respectively. Extraction of recyclables from residual waste led to avoided emissions for particulate matter, acidification and resource depletion impact categories. Marginal energy and the amount of energy recovered from landfill gas marginally affected the LCA results. On the contrary the quality of the recyclables extracted can significantly modify the eco profile of the management schemes.